FORMULATION AND EVALUATION OF LORNOXICAM MICROSPONGES USING EUDRAGIT RS 100 AND EUDRAGIT RSPO - Thireesha, Bannaravuri; Prasad, Ayya Rajendra; Peter P L, Haroled (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of the present study was preparation and evaluation of lornoxicam microsponges to prolong their drug release up to 12 h for effective osteoarthritis, rheumatoid arthritis, and acute lumbar-sciatica therapy. Methods: Lornoxicam microsponges were prepared by the quasi-emulsion solvent diffusion technique using different concentrations of polymers such as Eudragit RS 100 and Eudragit RSPO in ethanol and dichloromethane organic solvent mixture. Microsponges were evaluated for their particle size, percentage yield, entrapment efficiency, scanning electron microscopy (SEM), and in vitro drug release studies. Results: The percentage yield, entrapment efficiency, average particle size, and in vitro drug release for optimized formulation F12 were found to be 70.23% w/w, 81.34% w/w, 172.72 μm, and 96.64% up to 8 h, respectively. From SEM, it was observed that microsponges were found to be spherical in shape with rough surface texture. The formulation F12 shows zero-order release kinetics with an r2 value of 0.961 and the value of Korsmeyer–Peppas model was found to be 0.792; it follows super case II non-Fickian diffusion. The in vitro drug release studies showed that formulations comprised varying concentrations of Eudragit RSPO in higher proportion exhibited much-retarded drug release as compared to formulations comprised a higher proportion of varying concentrations of Eudragit RS 100. Conclusion: Among all the formulations F12 shows better results, which are released more than 80% of the drug release within 8 h; hence, it is optimized. These developed microsponges are releasing the drug for a longer period, which will be effective for osteoarthritis, rheumatoid arthritis, and acute lumbar sciatica therapy.